Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a, - 2 .( x + 6 ) + 6 . ( x - 10 ) = 8
- 2x - 12 + 6x - 60 = 8
4x - 72 = 8
4x = 8 + 72
4x = 80
x = 20
b, - 4 . ( 2x + 9 ) - ( - 8x + 3 ) - ( x + 13 ) = 0
- 8x - 36 + 8x - 3 - x - 13 = 0
- x - 52 = 0
x = - 52
c, 7x . ( 2 + x ) - 7x . ( x + 3 ) = 14
7x . ( 2 + x - x - 3 ) = 14
7x . ( - 1 ) = 14
7x = 14 : ( - 1 )
7x = - 14
x = - 2
d, 2 . ( 5 + 3x ) + x = 31
10 + 6x + x = 31
10 + 7x = 31
7x = 31 - 10
7x = 21
x = 3
a)-2(x+6)+6(x-10)=8
-2x+-12+6x+-60=8
4x+-72=8
4x=80
x=80:4
x=20
b)-4(2x+9)-(-8x+3)-(x+13)=0
-8x+-36+8x-3+x-13=0
(-8x+8x)+-36+-3+x-13=0
0+-52+x=0
x=0-(-52)
x=-52
c)7x(2+x)-7x(x+3)=14
14x+7x2
a) -32 -4.(x-5) = 0
<=>4.(x-5)=-32
<=>x-5=(-32):4
<=>x+5=-8
<=>x=-8+5
<=>x=-3
Vậy x=-3
b) 13.(x-5)=-169
<=>x-5=(-169):13
<=>x-5=-13
<=>x=-13+5
<=>x=-8
vậy x=-8
c) (-2).x+5 = (-3).(-3)+8
<=>(-2).x+5=17
<=>(-2).x=17-5
<=>(-2).x=12
<=>x=12:(-2)
<=>x=-6
Vậy x=-6
d) (-8).x = (-10).(-2)-4
<=>(-8).x=16
<=>x=16:(-8)
<=>x=-2
vậy x=-2
e) (-9).x+3 = (-2).(-7)+16
<=>(-9).x+3=30
<=>(-9).x=30-3
<=>(-9).x=27
<=>x=27:(-9)
<=>x=-3
Vậy x=-3
b) /x/ - 10 = -3
=> |x|=-3 + 10
|x|=7
=> x = 7 hoặc x= -7
a) 3x – 5 = -7 – 13
3x-5= -20
3x=-20+5
3x=-15
x=-15:3
x=-5
d) |2x – 5| –7 = 22
| 2x -5 | = 22+7
| 2x -5 | = 29
TH1: 2x-5 = -29
2x = -29+5
2x= -24
x= -24:2
x= -12
TH2: 2x -5 =29
2x = 29+5
2x= 34
x= 34:2
x= 17
Vậy...
a) \(-65-\left(x+15\right)+105=0\)
\(-65-\left(x+15\right)=-105\)
\(x+15=-65-\left(-105\right)\)
\(x+15=40\)
\(x=25\)
b) |-6| + (-9) - (x+1) = 7
-3- (x+1) =7
x+1 = -10
x = -11
c)\(\left|5-x\right|+\left(-25+7\right)=-3-\left(-10\right)\)
\(\left|5-x\right|+\left(-18\right)=7\)
\(\left|5-x\right|=25\)
\(\Rightarrow\orbr{\begin{cases}5-x=25\\5-x=-25\end{cases}\Rightarrow\orbr{\begin{cases}x=-20\\x=30\end{cases}}}\)
d) \(28-\left|x+6\right|+\left(-2\right)=0\)
\(28-\left|x+6\right|=2\)
\(\left|x+6\right|=26\)
\(\Rightarrow\orbr{\begin{cases}x+6=26\\x+6=-26\end{cases}\Rightarrow\orbr{\begin{cases}x=20\\x=-32\end{cases}}}\)
e) \(x-\left(13-15\right)=5+\left(10-x\right)-\left(-1\right)\)
\(x+2=5+10-x+1\)
\(x+2=16-x\)
\(x+x=16-2\)
\(2x=14\)
\(x=7\)
f) \(-120-\left(x-5\right)=125\)
\(x-5=-120-125\)
\(x-5=-245\)
\(x=-240\)
g) \(10-\left(-5+2\right)+\left(-9\right)=\left(-20+7\right)-x\)
\(-16=-13-x\)
\(x=-13+16\)
\(x=3\)
a. 3x-5=-7-13
3x-5=-20
3x=-20+5
3x=-15
x=-15:3
x=-5
b) |x|-10=(-3)
\(\Leftrightarrow\) |x|=(-3)+10=7
\(\Rightarrow\left[{}\begin{matrix}x=7\\x=-7\end{matrix}\right.\)
Vậy..............
c) x+2(x-9)=0
\(\Leftrightarrow\) (x-9)+2(x-9)=0-9=(-9)
\(\Leftrightarrow\) (x-9)(2+1)=(-9)
\(\Leftrightarrow\) 3(x-9)=(-9)
\(\Leftrightarrow\) x-9=(-9):3=(-3)
\(\Leftrightarrow\) x=(-3)+9=6
Vậy: x=6